2017
DOI: 10.1620/tjem.242.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Ability in Children Prenatally Exposed to Methylmercury: The 18-Month Follow-Up of Tohoku Study of Child Development

Abstract: Fish contain nutrients essential to the developing fetal brain, but they are contaminated with methylmercury. The Tohoku Study of Child Development, now underway in the Sanriku coastal area of Miyagi prefecture, Japan, follows mother-child pairs to examine the risks and benefits of fish consumption during pregnancy, especially the effects of prenatal exposures to methylmercury, selenium, and docosahexaenoic acid (DHA) on child neurodevelopment. Children aged 18 months were administered the Bayley Scales of Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
(62 reference statements)
1
25
0
Order By: Relevance
“…In support of this, a study that compared the KSPD with the Bayley-2, an older version of the Bayley-3, found that the KSPD score was higher than the Bayley-2 score, suggesting that the children identified as delayed on the KSPD were more severely delayed than those identified on the Bayley-2. 21 This supports our explanation of why the alternative criterion for the J-ASQ-3 worked better than the original criterion for distinguishing children who needed specialized support from those who did not in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…In support of this, a study that compared the KSPD with the Bayley-2, an older version of the Bayley-3, found that the KSPD score was higher than the Bayley-2 score, suggesting that the children identified as delayed on the KSPD were more severely delayed than those identified on the Bayley-2. 21 This supports our explanation of why the alternative criterion for the J-ASQ-3 worked better than the original criterion for distinguishing children who needed specialized support from those who did not in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…However, other studies failed to find any significant association with these and other assessed aspects of neuropsychological development in children from Greece (Kippler et al, 2016), USA (Oken et al, 2016), Poland (Polanska et al, 2016) and Japan (Tatsuta et al, 2017). Se levels (mean ± standard deviation) observed in these studies were 23 ± 8.6 µg/L in maternal urine at the first trimester of pregnancy in Greece (Kippler et al, 2016), 205.6 ± 34.6 ng/mL in erythrocytes at mid-pregnancy in USA (Oken et al, 2016), and 66.3 ± 10.2 and 67.0 ± 9.6 ng/g (for boys and girls, respectively) in cord plasma in Japan (Tatsuta et al, 2017). Conversely, Saint-Amour et al (2006) observed that prenatal Se levels were associated with alterations in the visual evoked potentials of Inuit children (cord blood Se was 4.44 ± 2.08 µmol/L) (Saint-Amour et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Excessive consumption of methylmercury-contaminated fish causes severe central nervous system injury, such as Minamata disease [2]. Recent epidemiological studies have suggested that excessive intake of 2 of 17 methylmercury during pregnancy has an adverse effect on fetal neural development [3,4]. However, the molecular mechanisms underlying methylmercury-induced central nervous system injury are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%